QoE-aware resource allocation for scalable video transmission over multiuser MIMO-OFDM systems - Li, Maodong (2013)
We investigate in this paper how to maximize multiuser Quality of Experience (QoE) when scalable videos are transmitted over Multiple-Input Multiple-Output (MIMO)-Orthogonal Frequency Division Multiplexing (OFDM) systems. We first study the QoE issues in Scalable Video Coding (SVC) adaptation by constructing a QoE assessment database. We derive the optimal scalability adaptation track for individual video and further summarize common scalability adaptation tracks for grouped videos. A rate-model is developed for SVC adaptation and is employed in designing an efficient resource allocation solution for SVC streaming over multiuser MIMO-OFDM systems. Specifically, time-frequency unit assignment, power allocation, and modulation selection are jointly optimized to maximize users' QoE. Experimental results show that the proposed QoE-aware scalability adaptation scheme significantly outperforms the conventional adaptation schemes, and the proposed QoE-aware resource allocation achieves better QoE performance when compared to existing resource allocation methods.